Population pharmacokinetics of riociguat and its metabolite in patients with chronic thromboembolic pulmonary hypertension from routine clinical practice. (January 2020) - Michaličková, Danica; Jansa, Pavel; Bursová, Miroslava; Hložek, Tomáš; Čabala, Radomír; Hartinger, Jan Miroslav; Ambrož, David; Aschermann, Michael; Lindner, Jaroslav; Linhart, Aleš; Slanař, Ondřej; Krekels, Elke H.J.
Pharmacokinetic data for riociguat in patients with chronic thromboembolic pulmonary hypertension (CTEPH) have previously been reported from randomized clinical trials, which may not fully reflect the population encountered in routine practice. The aim of the current study was to characterize the pharmacokinetic of riociguat and its metabolite M1 in the patients from routine clinical practice. A population pharmacokinetic model was developed in NONMEM 7.3, based on riociguat and its metabolite plasma concentrations from 49 patients with CTEPH. One sample with riociguat and M1 concentrations was available from each patient obtained at different time points after last dose. Age, bodyweight, sex, smoking status, concomitant medications, kidney and liver function markers were tested as potential covariates of pharmacokinetic of riociguat and its metabolite. Riociguat and M1 disposition was best described with one-compartment models. Apparent volume of distribution (Vd/F) for riociguat and M1 were assumed to be the same. Total bilirubin and creatinine clearance were the most predictive covariates for apparent riociguat metabolic clearance to M1 (CLf, M1 /F) and for apparent riociguat clearance through remaining pathways (CLe, r /F), respectively. CLf, M1 /F, CLe, r /F, Vd/F of riociguat and M1, and clearance of M1 (CLe, M1 /F) for a typical individual with 70 mL/min creatinine clearance and 0.69 mg/dL total bilirubin were 0.665 L/h (relative standard error = 17%)), 0.66 (18%) L/h, 3.63 (15%) L and 1.47 (19%) L/h, respectively. Upon visual identification of six outlying individuals, an absorption lag-time of 2.95 (6%) h was estimated for these patients. In conclusion, the only clinical characteristics related to riociguat exposure in patients with CTEPH from routine clinical practice are total bilirubin and creatinine clearance. This confirms the findings of the previous population pharmacokinetic studies based on data from randomized clinical trials.